Nickel-Catalyzed Regioselective Access to Dibenzo[b,e]Azepinones: Mechanistic Study, Docking, and Biophysical Exploration of Binding Interactions with Human Hemoglobin - Ahamed, Sk Shamim; Mandal, Uma Sankar; Bag, Sagar; Burman, Mangal Deep; Lo, Rabindranath; Manna, Debashree; Bhowmik, Sudipta; Ghosh, Tapas (Chemistry, an Asian journal, 2025)
A nickel-catalyzed intramolecular acetylene hydroarylation process has been described to produce dibenzo[b,e]azepin-6-one derivatives in an effective, regioselective manner. This procedure demonstrates a broad substrate scope and exceptional tolerance to various functional groups. Mechanistic insights were confirmed through the use of the density functional theory method. Selective synthesized compounds were subjected to biophysical analysis such as UV-vis absorption spectroscopy, fluorescence spectroscopy, stoichiometric analysis, thermal melting, and circular dichroism spectroscopic analysis revealing strong binding affinity to exploit their interactions with human hemoglobin (Hb). Additionally, molecular docking studies provided insights into the interactions between the synthesized molecule and human Hb.
Keywords: Protein Binding; Hemoglobins; nikl; Nickel; Nickel catalysis; vazebná místa; Intramolecular acetylene hydroarylation; molekulární struktura; Molecular Structure; Dibenzo[b,e]azepin‐6‐ones; Density Functional Theory; Molecular Docking Simulation; Human hemoglobin; hemoglobiny; simulace molekulového dockingu; teorie funkcionálu hustoty; vazba proteinů; Binding Sites; stereoizomerie; lidé; Humans; Azepines; DFT; Catalysis; azepiny; katalýza; Stereoisomerism